Representation of Anger through Nikita Mirzani’s Speech and Emotional Expression in the Hotman Paris Show Television Show 2019: - Irma Galuh Prameswari; Eko Suroso (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the representation of anger through speech and emotional expression displayed by Nikita Mirzani in the Hotman Paris Show in 2019 with a psycholinguistic review. This phenomenon is interesting to study because it shows how language plays a role not only as a means of communication, but also as a medium of complex psychological expression. This study uses a descriptive qualitative approach with data sources in the form of video recordings of events that show emotional interactions between Nikita Mirzani and Elza Syarief. The data analyzed included verbal speech and nonverbal expressions, such as intonation, gestures, and facial expressions, with the analysis of Miles and Huberman’s interactive models. Jakobson’s theory of language function and Plutchik’s theory of emotion are used as interpretive bases for relating linguistic and psychological dimensions in the expression of anger. The results of the study show that Nikita Mirzani’s form of anger is represented through four types of speech, namely emotive, referential, connotative, and fatis. The four forms of speech are accompanied by emotional expressions in the form of high pitches, physiological changes, and aggressive gestures. Emotive speech marks an outpouring of spontaneous emotions, referential speech shows fact-based self-defense, connotative speech expresses symbolic attacks, and fatis speech serves to maintain the continuity of interaction. The implications of this study show that anger as a psycholinguistic phenomenon is a form of multimodal communication that involves the interaction between cognitive processes, emotions, and language. Practically, the results of this research can be a reference for media practitioners, public communicators, and language educators in understanding and managing emotional expressions so that communication in public spaces remains ethical, effective, and balanced.